Pengaruh Tingkat Pendidikan, Pemahaman Akuntansi, Skala Usaha Dan Budaya Organisasi Terhadap Implementasi SAK EMKM (Studi Kasus Pada UMKM Kecamatan Banjar, Kabupaten Buleleng) - Dayu Putu Sri Agustini; I Gusti Ayu Purnamawati (Universitas Pendidikan Ganesha, 2022)
This study aims to determine the impact of education level, understanding of accounting, business scale, and organizational culture on the implementation of SAK EMKM. This research is a type of quantitative research that uses primary and secondary data. The population in this study is 222 UMKM in Banjar District. The sampling technique in this study was random sampling with a total of 69 respondents. Method of data collection using the method of documentation and questionnaires. Data analysis technique using multiple linier regression analysis using SPSS version 24 for windows. The results of the study show that: (1) education level has a positive and significant impact on the implementation of SAK EMKM, (2) understanding of accounting has a positive and significant impact on the implementation of SAK EMKM, (3) business scale has a positive and significant impact on the implementation of SAK EMKM, and (4) organizational culture has a positive and significant impact on the implementation of SAK EMKM, Kata Kunci: Education Level, Accounting Understanding, Business Scales, Organizational Culture, Implementation of SAK EMKM